Helter-Skelter Vocational Education R & D - Schaefer, Carl J.; National Academy of Sciences - National Research Council, Washington, DC. Div. of Behavioral Sciences ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
This paper focuses on the federal efforts in vocational research and development (R&D) of the last decade, reviewing major accomplishments, speculating on possible misdirections, and recommending directions for the future. The administration of vocational R&D is briefly described and a historical overview is presented of federal efforts from the passage of the vocational act of 1963 to the present status of funding. In addition to the administration's major accomplishment of providing visibility for vocational R&D, several specific accomplishments are enumerated, most of which indicate that the emphasis has been on developmental rather than on basic research. In speculating on possible alternatives to past directions, the change in emphasis from research to developmental priorities is traced from the point of view that the haste to operationalize has seriously decelerated vocational research efforts, channeling research monies into programmatic efforts and failing to engage in interdisciplinary research for a long enough period of time. In addressing the problem of how best to utilize the existing vocational research and development system for improvement, the author argues for more basic research to solve the sociological, psychological, and economic problems encountered in vocational education. An appeal is also made to the two national centers to return to their original mission of vocational R&D, and to the research coordinating units to focus more on research coordination. (NJ)
ERIC Note: Not available in hard copy due to marginal reproducibility of original document. For related papers see CE 009 020-025, CE 009 028-035, and ED 112 155.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Role; Educational Legislation; Educational Policy; Educational Research; Federal Legislation; Federal Programs; Needs Assessment; Research and Development Centers; Research Needs; State of the Art Reviews; Vocational Education; United States; Reports, Research